Sustainable Concrete Design Using Brown Chicken Eggshell to Reduce Carbon Footprint - Sulen, Camila (2024)
The construction industry, as well as the food industry, are two influential sectors in the economy of Peru. However, processes such as cement manufacturing for use in concrete production and the disposal of food waste are two of the main causes of environmental pollution globally. This research considers the use of brown chicken eggshell, typically considered waste in the food industry, to be used as a partial replacement for cement in concrete mixes. The experimental work conducted analyses the properties of concrete in a hardened state through destructive and non-destructive laboratory tests, evaluates the effectiveness of eggshell as a partial replacement for cement in three presentations: fresh eggshell, dried eggshell, and eggshell ash; and determines the variation in carbon footprint of the concrete with eggshell compared to the standard concrete mix. This sustainable approach not only improves the properties of concrete but also marks an important step towards sustainable construction and the reuse of food waste.